2021
DOI: 10.2196/25129
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Theories and Motivational Features Underlying eHealth Interventions for Adolescent Antiretroviral Adherence: Systematic Review

Abstract: Background eHealth systems provide new opportunities for the delivery of antiretroviral therapy (ART) adherence interventions for adolescents. They may be more effective if grounded in health behavior theories and behavior change techniques (BCTs). Prior reviews have examined the effectiveness, feasibility, and acceptability of these eHealth systems. However, studies have not systematically explored the use of health behavior theories and BCTs in the design of these applications. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…Previous studies recommend that a solid theoretical foundation is necessary to plan, design, evaluate, and implement eHealth self-management interventions [ 69 ]. However, our review found that only a few eHealth CKD self-management interventions reported the use of a specific theory [ 21 ], thereby limiting the understanding of mechanisms of action and hindering replication of eHealth intervention implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies recommend that a solid theoretical foundation is necessary to plan, design, evaluate, and implement eHealth self-management interventions [ 69 ]. However, our review found that only a few eHealth CKD self-management interventions reported the use of a specific theory [ 21 ], thereby limiting the understanding of mechanisms of action and hindering replication of eHealth intervention implementation.…”
Section: Discussionmentioning
confidence: 99%
“…MASI includes multiple BCTs to address the various complex barriers to adherence experienced by adolescents and young adults. Other studies have found that interventions with more BCTs are more effective than those with a limited amount of BCTs [ 23 , 58 ]. The multiple BCTs are integrated into a variety of features within the MASI app that allows users to explore and use features that are most helpful and desirable to them.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their promise, few digital health interventions to date have been developed and tested with adolescents and young adults in Eastern or Southern Africa. Among those that have been evaluated, basic applications such as SMS text messaging and phone calls have been the most common [ 23 ]. The findings of such SMS text messaging–delivered interventions have been mixed [ 24 ], highlighting the limitations of addressing only 1 adherence challenge (eg, forgetfulness), and underscoring the potential of incorporating multiple behavior change techniques (BCTs) to comprehensively address the varied adherence barriers experienced by adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…To further implement, the respective settings need to consider the training of nurses and case managers that can influence and educate PLWHA [ 61 ]. For smartphone-based interventions, the availability of smartphones to PLWHA and their literacy level to use the smartphone applications are crucial before implementation [ 62 , 63 ]. A recent randomized-controlled trial (RCT) reported that smartphone-based adherence intervention was convenient to implement and easy to use for the overwhelming majority of participants, and PLWHA found the intervention useful and highly acceptable overall [ 62 ].…”
Section: Discussionmentioning
confidence: 99%